Evaluation of Oncogene NUP37 as a Potential Novel Biomarker in Breast Cancer - Li, Kangdi; Liu, Ting (Frontiers in Oncology, 2021)
Abstract Purpose: There is an urgent need to identify oncogenes that may be beneficial to diagnose and develop target therapy for breast cancer. Methods: Based on the GEO database, DECenter was used to screen the differentially overexpressed genes in breast cancer samples. Search Tool for the Retrieval of Interacting Genes and Cytoscape were performed to construct the PPI network to predict the hub gene. Functional and pathway enrichment were performed based on GO analysis. GEO2R, Oncomine, human tissue microarray staining and western blot were applied to confirm the expression of NUP37. The association between NUP37 expression and prognosis in patients with breast cancer were assessed using the Kaplan–Meier plotter online tool and OncoLnc. siRNAs were used to knockdown NUP37 and evaluate proliferation, migration and stemness in breast cancer cells. Results: We found that 138 genes were differentially upregulated in breast cancer samples, mainly comprising components of the nucleus and involved in the cell cycle process. NUP37 was identified as a hub gene that is upregulated in breast cancer patients related to a significantly worse survival rate. Furthermore, we confirmed that the downregulation of NUP37 in breast cancer cell result in the inhibition of cell growth, migration and stemness. Conclusions: High expression of NUP37 in breast cancer patients is associated with a poorer prognosis and promote cell growth, migration and stemness. The multiple bioinformatics and experimental analysis help provide comprehensive understanding of the roles of NUP37 as a potential marker for diagnosis and prognosis and as a novel therapeutic target in breast cancer.